Atomistic investigation of the interfacial mechanical characteristics of carbon nanotube reinforced epoxy composite. (August 2015) - Xiong, Q.L.; Meguid, S.A.
Graphical abstract: Highlights: Load transfer in nanocomposites is governed by the interface strength. Investigated the interface strength of CNT–epoxy composites using pull-out tests and MD. The work reveals that the ISS is governed by the geometry of the CNT. The cut-off distance of the L-J has a marginal effect on ISS. Incorporation of an end cap in the pull-out test leads to a greater pull-out peaks. Abstract: In this work, we investigate the interfacial mechanical characteristics of carbon nanotube (CNT) reinforced epoxy composite using molecular dynamics (MD) simulations. The MD simulations were carried out by developing two pull-out models; namely, the displacement-load model and the velocity-load model. The second-generation force field – polymer consistent force field (PCFF) – is used in the current MD simulations. The effects of various parameters, such as epoxy density, length and diameter of a CNT, the CNT–epoxy interfacial thickness, LJ cut-off distance and capping conditions of a CNT on the interfacial mechanical characteristics have also been investigated and discussed. The results from the present pull-out model, which are validated with earlier studies, reveal that (i) the interfacial shear strength (ISS) of the CNT-reinforced epoxy composite is improved with the increase in the epoxy density, (ii) the ISS of the CNT-reinforced epoxy composite decreases with the increase in the values of length and diameter of a CNT, and the thickness of CNT–epoxy matrix interface, (iii) the LJ cut-off distance has marginal effect on the ISS and the pull-out force of CNT, and (iv) incorporation of an end cap in the simulations results high initial pull-out peaks, which well correlate with the experimental findings.